The SL(K+3,C) symmetry of string scatterings from D-branes - Sheng-Hong Lai; Jen-Chi Lee; Yi Yang (Nuclear Physics B, 2023)
By using the solvability of Lauricella function FD(K)(α;β1,...,βK;γ;x1,...,xK) with nonpositive integer βJ, we show that each scattering or decay process of string and D-brane states at arbitrary mass levels can be expressed in terms of a single Lauricella function. This result extends the previous exact SL(K+3,C) symmetry of tree-level open bosonic string theory to include the D-brane.